DESIGN IMPROVEMENT OF COMBUSTION CHAMBER OF TURBOJET TJ-24 - ALFARISI (NIM : 13113065), AZHAR
Turbojet model development in Indonesia is not done yet. The design process is done either mathematically or trial and error in order to achieve optimal design. At ITB the development of turbojet model started by Grace in 2002 with the name TJ-24 (24 Newton). Test results showed TJ-24 did not achieve idle operation. In 2013, Eira made improvements with the TJ-24 achieving idle operation and achieving thrust of 13 N. The cause of the non-24 N thrust force was likely to come from both design and manufacturing sides. After that, in 2017 Andrew and Bima made improvements but there was jamming problem in the bearing so that TJ-24 could not operate. Design improvement and manufacturing process needed to be done in order to produce a turbojet model, especially the combustion chamber that capable to support the TJ-24 operation. This improvement began with evaluating the previous TJ-24. With the results of the evaluation, the simulation was done on the rotor components and combustion chamber by using the software to predict the phenomenon that occurs, and became the reference for the calculation process. Then trial and error process and mathematical calculations were done to validate the simulation. After that, design improvement of components and testing of TJ-24 operation were done. The results showed that operating rpm had not reached design rpm, thrust of 1 N, and failure of the turbine. TJ-24 did not reach idle condition since the produced thrust did not achieve idle thrust (2,4 N).